Mental Health and Daily Activities of Retired Elderly People(Males) of Kolkata in the Wake of Second Wave of Covid-19 (Journal of Pharmaceutical Negative Results, 2022)
The present online study was an attempt to assess the mental health and daily activities of 60 public sector retirees, selected from Kolkata city areas through the snowball sampling method, during the second wave of Covid-19. To measure the mental health and to assess the daily activity status, Mental Health Inventory(Local adaptation by Jagdish&Srivastav, 1983) and a self-devised questionnaire respectively were used. The findings of the study revealed that the state of mental health of older retirees was worse than that of the younger retired group. Also, their activity level was lower compared to the latter. Besides, the condition of all retirees as a whole worsened because of remaining confined at home more than their frailing health. The covid pandemic had more impact on the mental health of the older group than the younger group, which were suffering more from covid induced mental illnesses. On the basis of the present findings, it is suggested that the family members, counselors, and health professionals should plan a strategy to combat the mental health issues of such elderly people.